Kelvin John Lancaster and the distinction between the "goods are goods" approach and the "characteristics" approach to demand theory - Julien Gradoz (Duke University, Center for the History of Political Economy (CHOPE), 2024)
In demand theory, the "characteristics approach" refers to situations where goods are described according to their characteristics. This approach is often contrasted with the "goods are goods" approach. We trace the origin of this expression back to a critique of demand theory formulated by Harry Johnson in 1958, which complete a critique proposed by Kelvin John Lancaster in 1957. We demonstrate that Johnson's interpretation of this expression does not align with the interpretation that later became dominant in demand theory. We also highlight that these articles are connected with the development of the characteristics approach by Lancaster in the 1960s.
Keywords: B21; D11; 330; Kelvin John Lancaster; characteristics; demand theory; Harry Gordon Johnson; John Richard Hicks